OPFython: A Python implementation for Optimum-Path Forest - de Rosa, Gustavo H.; Papa, João P. (Software impacts, 2021)
OPFython is an open-sourced Python package that implements Optimum-Path Forest algorithms using object-oriented programming and a straightforward structure. It provides an alternative implementation to the standard LibOPF package, which heavily depends on the C language and occasionally hinders fast prototyping. Additionally, OPFython provides documented code, unitary tests, and examples that assist users in learning how to work with the package. Such features are well-suited for researchers and developers interested in exploring alternative state-of-the-art machine learning algorithms. •Python-based open-source Optimum-Path Forest framework.•OPFython implements the same structured proposed by LibOPF.•Composed of pre-defined classes and methods that allows faster prototyping.•Allows usage of modern programming paradigms, such as object-oriented and JSON input data.